Anti-Cancer Effects of Pristimerin and the Mechanisms: A Critical Review - Li, Jia-jun; Yan, Yan-yan; Sun, Hong-mei; Liu, Yun; Su, Chao-yue; Chen, Hu-biao; Zhang, Jian-ye (Frontiers in Pharmacology, 2019)
As a a quinonemethide triterpenoid extracted from species of the Celastraceae and Hippocrateaceae, pristimerin has been shown to have potent anti-cancer effects. Specifically, it was found that pristimerin can affect many tumor-related processes including vasculogenesis, autophagy, epithelial-mesenchymal transition and ubiquitin-proteasomal degradation, as well as involving various molecular targets and signaling pathways such as cyclins, reactive oxygen species caspase-3, and NF-κB, MAPK/ERK and AKT/mTOR pathways. In this review, we will focus on the the research about anti-cancer effacy of pristimerin to achieve a deeper understanding of the targets and mechanisms, which offers evidences suggesting that pristimerin can be a potent anti-cancer drug.